2013
DOI: 10.2337/dc12-2454
|View full text |Cite
|
Sign up to set email alerts
|

Adding Once-Daily Lixisenatide for Type 2 Diabetes Inadequately Controlled by Established Basal Insulin

Abstract: OBJECTIVETo examine the efficacy and safety of adding the once-daily glucagon-like peptide-1 receptor agonist (GLP-1RA) lixisenatide to established basal insulin therapy alone or together with metformin, in people with type 2 diabetes and elevated glycated hemoglobin (HbA1c).RESEARCH DESIGN AND METHODSWe conducted a double-blind, parallel-group, placebo-controlled trial. Patients (n = 495) with established basal insulin therapy but inadequate glycemic control were randomized to add lixisenatide 20 μg or placeb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

34
342
9
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 264 publications
(396 citation statements)
references
References 26 publications
(28 reference statements)
34
342
9
5
Order By: Relevance
“…The incidence of antibodies in the present study was lower than in other GLP‐1 compounds with an exendin‐4 backbone (exenatide twice daily, 44–60% 32; exenatide once weekly, 61–68% 33, 34; and lixisenatide, approximately 70% 35); the lower incidence in the present study is probably attributable to the design of the dulaglutide molecule 36.…”
Section: Discussioncontrasting
confidence: 73%
“…The incidence of antibodies in the present study was lower than in other GLP‐1 compounds with an exendin‐4 backbone (exenatide twice daily, 44–60% 32; exenatide once weekly, 61–68% 33, 34; and lixisenatide, approximately 70% 35); the lower incidence in the present study is probably attributable to the design of the dulaglutide molecule 36.…”
Section: Discussioncontrasting
confidence: 73%
“…Lixisenatide was associated with a pronounced improvement in postprandial hyperglycaemia compared with placebo in these studies,25, 26, 27, 29 including studies in Asian patients exclusively 28, 30. Further, lixisenatide had a greater postprandial effect on blood glucose levels than the longer‐acting GLP‐1 receptor agonist liraglutide in patients with T2D insufficiently controlled on metformin, with or without insulin glargine 31, 32…”
Section: Introductionmentioning
confidence: 86%
“…Lixisenatide (Lyxumia ® , Adlyxin ® ; Sanofi, Paris, France) is a once‐daily (QD), prandial, short‐acting GLP‐1 RA that has been evaluated extensively in the large, phase 3 GetGoal clinical trial program carried out in approximately 50 countries including Japan11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21. Treatment with lixisenatide monotherapy in patients with type 2 diabetes mellitus has shown improved glycemic control with reduced HbA1c, postprandial plasma glucose, fasting plasma glucose (FPG) and bodyweight, and has been shown to be well tolerated11, 12, 13.…”
Section: Introductionmentioning
confidence: 99%
“…Treatment with lixisenatide monotherapy in patients with type 2 diabetes mellitus has shown improved glycemic control with reduced HbA1c, postprandial plasma glucose, fasting plasma glucose (FPG) and bodyweight, and has been shown to be well tolerated11, 12, 13. Lixisenatide has also shown improved glycemic control as an add‐on treatment (including basal insulin with or without SU, metformin, metformin with or without SU, pioglitazone with or without metformin, and SU with or without metformin)12, 14, 15, 16, 17, 18, 19. More specifically, subanalyses of two randomized, placebo‐controlled studies in patients with type 2 diabetes mellitus, GetGoal‐S12 (lixisenatide add‐on to SU with or without metformin) and GetGoal‐L‐Asia (lixisenatide add‐on to basal insulin with or without SU)14, showed that lixisenatide treatment provided glycemic control (decreased HbA1c, FPG and postprandial plasma glucose), and was well tolerated in the Japanese subpopulation22, 23.…”
Section: Introductionmentioning
confidence: 99%